Assessment of the anemic syndrome in the elderly - Nelson Rafael Terry Leonard; Carlos A. Mendoza Hernández; Yakelín Meneses Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Anemia is a common condition in the elderly and is a risk factor due to the increase in morbidity and mortality at this stage of life, which reduces not only the functional capacity and mobility, but also the quality of life. It constitutes a special health problem in the elderly due to its high prevalence. Its predominance increases with age, but it should not be considered as an unavoidable consequence of aging, but as the result of a high frequency of anemic diseases that are observed with repeatedly at this stage of life. The aim of this bibliographical review is to compile the different studies conducted on this topic and to describe the various causes of anemic syndrome in this age group. Its pathophysiology, negative effects and different complications are summarized.